ترجمة الآيات المتشابهات لصفات الله في "تفسير فيمفينن الرحمن": دراسة تحليلية من منظور نظريتي الترجمة لنيومارك وفيني وداربلني - محمد شفيف بن فائز
Anthropomorphic verses (Mutasyabihat) that consist of Attributes of Allah are those verses which have many interpretations. Thus, the meaning of these verses must be interpreted based on the context that is equivalent to the attributes of Allah SWT according to the methods of Arabic language disciplines. Anthropomorphic verses and their translations into the target language are widely debated by researchers, but there are not many studies that concentrate on the context of modern translation theories. Thus, this study attempts to discover this issue using two main translation theories, firstly, Componential Analysis theory introduced by Newmark (1988) to explore the meaning provided for each anthropomorphic words and secondly by Vinay and Darbelnet theory (1995) that aims to examine the translation methods applied in the translation of anthropomorphic verses. This study employs a qualitative approach through text analysis method. Seven anthropomorphic words were selected and elaborated descriptively: al-wajh, al-cain, al-yad, al-sāq, al- culuw, al-istiwā’, al-ityān atau al-maji’. The Qur'an translation namely "Tafsir Pimpinan ar-Rahman" by Abdullah Basmeih serves as the study corpus. The findings shows that the anthropomorphic words are mostly translated in accordance with the exact meanings of Attributes of Allah as mentioned in the exegeses, but there are translations that did not describe the attributes of Allah clearly in certain places. It is also found that Abdullah Basmeih’s translation of the verses is inclined towards the oblique translation as to achieve equivalent meanings, as well as giving explanations in parentheses and footnotes in order to render the meaning of anthropomorphic words. Therefore, some implications were identified such as the translation of anthropomorphic verses should not be translated literally, but it should be refer to the Quranic exegeses and dictionaries so the intended meanings are appropriate to feature the attributes of Allah SWT.